Exposed Collagen In Resin Bonds to Caries-affected Dentin After Dentin Treatment with Aqueous and Alcoholic Chlorhexidine Solutions - Ricci, Herica Adad [UNESP]; Salles Scheffel, Debora Lopes [UNESP]; Mariusso, Matheus Racy [UNESP]; Palomari Spolidorio, Denise Madalena [UNESP]; Souza Costa, Carlos Alberto de [UNESP]; Hebling, Josimeri [UNESP] (Quintessence Publishing Co Inc, 2014)
Purpose: To evaluate the effect of saturation of demineralized dentin with aqueous and alcoholic excipients of chlorhexidine (CHX) on the exposure of collagen fibrils in resin-dentin bonds in sound and caries-affected dentin.Materials and Methods: Flat midcoronal dentin surfaces were prepared from 24 noncarious molars, and artificial caries was induced in half of the sample. For each substrate, the surfaces were assigned to 4 groups (n = 3) according to the saturation solution of the dentin: water, ethanol, 1% CHX aqueous or alcoholic solution. Infected dentin was removed by abrasive papers. After acid etching, the dentin surface was saturated with each solution for 60 s followed by application of Single Bond. The specimens were processed for Goldner's trichrome staining and the thickness of the exposed collagen zone (ECZ) at the resin/dentin interfaces was measured under optical microscopy. Data were analyzed statistically by Kruskal-Wallis and Mann-Whitney tests (alpha = 0.05).Results: Regardless of the saturation solution, caries-affected dentin presented a thicker ECZ at the bottom of the hybrid layer than did sound dentin. For both substrates, 100% ethanol had a negative influence on collagen exposure in comparison with water, but the same was not observed for the CHX alcoholic solution. CHX solutions did not differ significantly from each other or from their respective solvents.Conclusion: The saturation of phosphoric acid-demineralized dentin with either CHX aqueous or alcoholic solutions did not affect the exposure of collagen fibrils in the resin-dentin bonds produced in sound and caries-affected dentin. A thicker zone of exposed collagen was found in hybridized caries-affected dentin compared to noncarious dentin.
Keywords: dental caries; dentin bonding agents; dentin; ethanol; chlorhexidine